Rise and Fall of the East Asian Growth System, 1950-1999. - Huang, Xiaoming (RoutledgeCurzon, 2004)
This book examines the long run of economic growth in East Asia from 1945 to the present, assessing the various theories put forward to explain the phenomenon, and appraising the various factors which have contributed to economic growth in East Asia.